Central and systemic IL-1 exacerbates neurodegeneration and motor symptoms in a model of Parkinson‘s disease - Pott Godoy, María Clara (2008)
Parkinson's disease is a neurodegenerative disorder with uncertain aetiology and ill-defined pathophysiology. Activated microglial cells in the substantia nigra (SN) are found in all animal models of Parkinson's disease and patients with the illness. Microglia may, however, have detrimental and protective functions in this disease. In this study, we tested the hypothesis that a sub-toxic dose of an inflammogen (lipopolysaccharide) can shift microglia to a pro-inflammatory state and exacerbate disease progression in an animal model of Parkinson's disease. Central lipopolysaccharide injection in a degenerating SN exacerbated neurodegeneration, accelerated and increased motor signs and shifted microglial activation towards a pro-inflammatory phenotype with increased interleukin-1β (IL-1β) secretion. Glucocorticoid treatment and specific IL-1 inhibition reversed these effects. Importantly, chronic systemic expression of IL-1 also exacerbated neurodegeneration and microglial activation in the SN. In vitro, IL-1 directly exacerbated 6-OHDA-triggered dopaminergic toxicity. In vivo, we found that nitric oxide was a downstream molecule of IL-1 action and partially responsible for the exacerbation of neurodegeneration observed. Thus, IL-1 exerts its exacerbating effect on degenerating dopaminergic neurons by direct and indirect mechanisms. This work demonstrates an unequivocal association between IL-1 overproduction and increased disease progression, pointing to inflammation as a risk factor for Parkinson's disease and suggesting that inflammation should be efficiently handled in patients to slow disease progression.